Corrosion inhibition of C38 steel by alkaloids extract of Geissospermum laeve in 1 M hydrochloric acid: Electrochemical and phytochemical studies. (March 2015) - Faustin, M.; Maciuk, A.; Salvin, P.; Roos, C.; Lebrini, M.
Highlights: Geissospermum laeve alkaloids are corrosion inhibitors for C38 steel in 1 M HCl. Maximal inhibition efficiency is 92% at 25 °C with 100 mg/L of alkaloids extract. The studied extract resists to corrosion efficiently even at higher temperature. The main active molecule of the extract is geissospermine characterized by NMR. Abstract: Corrosion inhibition by alkaloids extract (AE) from Geissospermum laeve on C38 steel in 1 M HCl is investigated with electrochemical studies. Inhibition efficiency of 92% is reached with 100 mg/L of AE at 25 °C. Potentiodynamic polarization showed that the extract behaves as mixed-type inhibitors. The Nyquist plots showed that increasing AE concentration, charge-transfer resistance increased and double-layer capacitance decreased, involving increased inhibition efficiency. Adsorption of the inhibitor molecules corresponds to Langmuir adsorption isotherm. Immersion time and temperature effects were investigated using EIS and potentiodynamic polarization. SEM and EDX supported the adsorption conclusions. The active compound responsible for the corrosion inhibition is geissospermine.